Determination of Histamine in Various Marine Fish Species Available in Major Markets of Punjab, Pakistan by LC-MS/MS - Hadyait, Muhammad Arfan; Ali, Asif; Bhatti, Ehsan Mahmood; Qayyum, Aroosa; Ullah, Muhammad Aafar (PSM Biological Research, 2018)
Fish samples from selected five (5) major markets of Punjab (Lahore, Faisalabad, Multan, Rawalpindi and Gujranwala) were collected randomly consisting of nine (9) marine fish species. LCQ Fleet with ion trap mass analyzer coupled with Surveyorplus pump and Surveyorplus degassor of Thermoscientific was used for histamine determination in present study. The histamine detected in different nine (9) samples from different markets was within safe limits. The fishes were also examined for appearance, texture, odour and presence of black spots. All the physical parameters were within normal range. It was concluded that the marine fish species being sold in various fish markets of Punjab province are fresh with good physical conditions and having histamine in safe limits.